Manajemen Kesiswaan dalam Meningkatkan Prestasi Peserta Didik di MAN 5 Jombang - Umar Hadi; Ashari Ashari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Student management is needed to improve student achievement. Students will achieve maximum achievement with good management. Therefore, it is necessary to have effective student management in regulating all activities related to students so that educational goals are achieved efficiently.The objectives of this research are: 1) Analyzing the planning of student affairs management in improving student achievement at MAN 5 Jombang, 2) Analyzing the organization of student management in improving student achievement in MAN 5 Jombang, 3) Analyzing the implementation of student management in improving student achievement in MAN 5 Jombang, 4) Analyzing the evaluation of student management in improving student achievement in MAN 5 Jombang.The research approach used is qualitative with the type of case study in MAN 5 Jombang. Data collection techniques through observation, interviews, and documentation. The analysis is carried out during data collection and after all data is collected. The validity test of the data is carried out with credibility standards.The results of this study show that: 1) Student management planning in improving student achievement is planned at the beginning of the year and praised by the head of the madrasah, teachers and supervisors. Planning includes PPDB Planning, Olympic programs, and extracurricular programs. 2) The implementation of student management in improving student achievement is coordinated with the head of the madrasah, deputy head of the madrasah, teachers, Olympic Coaches, and extracurricular Coaches, as well as students. 3) Evaluation of student management in improving student achievement by assessing in accordance with their respective fields, both academic and non-academic by teachers and coaches who are experts in their fields.